Identifying Bullying and Its Relationship with Mental Health Problem Among Adolescents: A Scoping Review - Amin, Yusron; Haswita, Haswita (Indonesian Journal of Global Health Research, 2024)
Bullying action was still as trend and current issue, especially among adolescence. This was related to increasing incidence per year and its large impact especially on mental health problems. Where adolescence's mental health was a long-term asset because of its influence on development level and quality of life among adolescents in the future. The study aims was to identify bullying and its relationship with mental health problem among adolescence. The study design was a scoping review. The searching literature using journal database PubMed (MEDLINE), Proquest, ScienceDirect, and Google Scholar through entering keywords bullying, mental health problem, adolescence. 12 articles selected from 384 articles. It reported that increasing bullying incidents among adolescence were associated with gender, age, role in bullying, and type of bullying. Majority adolescence who experience bullying were at high risk of experiencing mental health problem especially depression, anxiety, and even suicidal idea and perpetration. There were correlation between bullying incidence with mental health problem among adolescence. The study result expecting could give an understanding to adolescence regarding to bullying and its huge negative impact on mental health, so that bullying action among adolescence could be stopped.